Evaluation of Angular Parameters of Craniocervical Junction and Establishing their Relevance in the Diagnosis of Basilar Invagination - Singh, Kulwant; Yadav, Vikrant; Prasad, Ravi Shankar; Sahu, Anurag; Pandey, Nityanand (Indian Journal of Neurosurgery, 2025)
The craniocervical junction (CCJ), composed of the atlas, axis, and occipital bone, is a critical anatomical consideration incorporating vital osseoligamentous and neurovascular structures. Basilar invagination (BI) is one of the most common CCJ anomalies. Elaborative research has been done on different linear craniometric parameters for diagnosing BI, but the role of the angular craniometric parameters is still under research. This study aims to describe a detailed analysis of the angular craniometric parameters in the population of the northern part of India. We also aim to describe the different angular craniometric parameters that are useful in establishing the diagnosis of BI.A total of 49 patients who underwent surgery for BI and met the criteria for the required bony landmarks used in the angular craniometric analysis were included in this study. Angular craniometric analysis was also performed for 120 controls who were screened for head and spine injuries following trauma, and subsequent scans showed no sign of radiological abnormalities.In this study, 49 patients were analyzed, who underwent surgery for BI, of which 67.35% (n = 33) patients were males and 32.65% (n = 16) were females. The values of Boogard's angle (BgA) greater than 145 degrees and foramen magnum angle (FMA) greater than 18 degrees were highly diagnostic of BI, with 99.41 and 100% diagnostic accuracies, respectively. Similarly, the value of the tentorial twinning line angle (TtwA) less than 31.9 degrees was highly diagnostic of BI with diagnostic accuracy of 78.11%. The diagnostic accuracy of the combination of TtwA with BgA (91.12%) and with FMA (91.72%) was higher than that of TtwA alone.FMA and BgA have excellent diagnostic accuracy for BI. TtwA can also be used for establishing the diagnosis of BI in the congenital occipital bone anomalies and comparison of preoperative and postoperative measurements following the surgical procedure like foramen magnum decompression.
Keywords: craniocervical junction; basilar invagination; Boogard's angle; foramen magnum angle; tentorial twinning line angle